2010
DOI: 10.1055/s-0029-1245752
|View full text |Cite
|
Sign up to set email alerts
|

Elektronisch erfasste Okklusionstherapie bei über 7-jährigen Amblyopen: Visusanstieg noch nach mehr als 4 Monaten?

Abstract: The patients presented here were able to integrate daily occlusion lasting several hours and the electronic monitoring of occlusion treatment into their daily routine over a period of 12 months. During this period the VA of all included types of amblyopia improved significantly, both from a clinical and statistical point of view. Further long-term studies using ODMs with larger groups of patients may identify factors for success of treatment, reveal the long-term stability of the improvement and contribute to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
2
4
0
1
Order By: Relevance
“…Conversely, other authors have reported significant improvement in amblyopic eye visual acuity in children older than 7 years. 19, 20 …”
Section: Discussionmentioning
confidence: 99%
“…Conversely, other authors have reported significant improvement in amblyopic eye visual acuity in children older than 7 years. 19, 20 …”
Section: Discussionmentioning
confidence: 99%
“…Crowded Landolt ring charts with optotype separation 2.6 minarc (Oculus, Wetzlar, Germany) presented at 40 cm distance were used for all patients. Occlusion was recorded using more recent versions of the ODM developed in the Netherlands (Simonsz et al, 1999), which were tested and applied for continuous recording in several previous studies (Awan, Proudlock, & Gottlob, 2005;Chopovska et al, 2005;Fronius, Bachert, & Lüchtenberg, 2009;Fronius et al, 2006;Kracht et al, 2010). Being taped to the occlusion patch, they measure the temperature difference between the patch on the eye and the surroundings.…”
Section: Participant Inclusion and Assessmentmentioning
confidence: 99%
“…Some of these data were also analyzed in the context of methodological studies assessing the practicability of continuous electronic recording of occlusion in patients of various ages (Chopovska et al, 2005;Fronius, Bachert, & Lüchtenberg, 2009;Fronius et al, 2006;Kracht et al, 2010). The periods of 1 and 4 months were chosen for the present analysis in order to include the rapid initial changes as well as the time span during which most of the improvement occurs according to previous reports (Kracht et al, 2010;Pediatric Eye Disease Investigator Group, 2003;Stewart et al, 2007b). This is a period during which hardly any changes in prescription are necessary, and during which the majority of the patients may be followed without too many drop-outs.…”
Section: Data Analysis Statisticsmentioning
confidence: 99%
“…Follow-up examinations were performed every 4 weeks in the first 4 months, then at the sixth, ninth and twelfth month. The extended time span of 12 months was chosen due to the eccentric fixation of the amblyopic eye and the large age span also including older children [31,36]. Visual acuity test and orthoptic assessment, including measuring the angle of squint (using cover/uncover and alternate cover test with prisms), examining binocular vision and assessing fixation of both eyes were executed on every followup examination.…”
Section: Study Design and Patient Inclusionmentioning
confidence: 99%